Comparative transcriptomics reveal stage-dependent parasitic adaptations in the myxozoan Sphaerospora molnari - Wiśniewska, Monika M; Kyslík, Jiří; Alama-Bermejo, Gema; Lövy, Alena; Kolísko, Martin; Holzer, Astrid S; Kosakyan, Anush (BMC genomics, 2025)
BACKGROUND: Parasitism as a life strategy has independently evolved multiple times within the eukaryotic tree of life. Each lineage has developed mechanisms to invade hosts, exploit resources, and ensure replication, but our knowledge of survival mechanisms in many parasitic taxa remain extremely limited. One such group is the Myxozoa, which are obligate, dixenous cnidarians. Evidence suggests that myxozoans evolved from free-living ancestors to endoparasites around 600 million years ago and are likely one of the first metazoan parasites on Earth. Some myxozoans pose significant threats to farmed and wild fish populations, negatively impacting aquaculture and fish stocks; one such example is Sphaerospora molnari, which forms spores in the gills of common carp (Cyprinus carpio), disrupting gill epithelia and causing somatic and respiratory failure. Sphaerospora molnari undergoes sequential development in different organs of its host, with large numbers of morphologically distinct stages occurring in the blood, liver, and gills of carp. We hypothesize that these parasite life-stages differ in regards to their host exploitation, pathogenicity, and host immune evasion strategies and mechanisms. We performed stage-specific transcriptomic profiling to identify differentially expressed key functional gene groups that relate to these functions and provide a fundamental understanding of the mechanisms S. molnari uses to optimize its parasitic lifestyle. We aimed to identify genes that are likely related to parasite pathogenicity and host cell exploitation mechanisms, and we hypothesize that genes unique to S. molnari might be indicative of evolutionary innovations and specific adaptations to host environments. RESULTS: We used parasite isolation protocols and comparative transcriptomics to study early proliferative and spore-forming stages of S. molnari, unveiling variation in gene expression between each stage. We discovered several apparent innovations in the S. molnari transcriptome, including proteins that are likely to function in the uptake of previously unknown key nutrients, immune evasion factors that may contribute to long-term survival in hosts, and proteins that likely improve adhesion to host cells that may have arisen from horizontal gene transfer. Notably, we identified genes that are similar to known virulence factors in other parasitic organisms, particularly blood and intestinal parasites like Plasmodium, Trypanosoma, and Giardia. Many of these genes are absent in published cnidarian and myxozoan datasets and appear to be specific to S. molnari; they may therefore represent potential innovations enabling Sphaerospora to exploit the host's blood system. CONCLUSIONS: In order to address the threat posed by myxozoans to both cultured fish species and wild stocks, it is imperative to deepen our understanding of their genetics. Sphaerospora molnari offers an appealing model for stage-specific transcriptomic profiling and for identifying differentially expressed key functional gene groups related to parasite development. We identified genes that are thus far unique to S. molnari, which reveal their evolutionary novelty and likely role as adaptations to specific host niches. In addition, we describe the pathogenicity-associated genetic toolbox of S. molnari and discuss the implications of our discoveries for disease control by shedding light on specific targets for potential intervention strategies.
Keywords: Transcriptome; Differential expression; Gene Expression Profiling; Gills; stanovení celkové genové exprese; Host-Parasite Interactions; interakce hostitele a parazita; Adaptation, Physiological; Animals; Sphaerospora molnari; Myxozoa; Species specific genes; Myxozoans; zvířata; transkriptom; Pathogenicity related; fyziologická adaptace; kapři; Carps; žábry